Potential of Coffee Fruit Waste as Main Product of Benteng Alla Utara Village, Enrekang Regency - Base, Nurul Hidayah; Usman, Musrayani; As’ad, Ihwana; Asbar; Noena, Raymond Arief N. (Indonesian Journal of Community Services Cel, 2022)
Farmers in Enrekang Regency, especially in Benteng Alla Utara Village, generally manage coffee plantations as their source of livelihood. The type of coffee produced is Arabica Kalosi Enrekang which is known to have a taste and aroma favored by coffee connoisseurs. Coffee beans are produced to meet the needs of foreign exports in quite large quantities. Processed waste of coffee cherries in the form of coffee pod skins is a waste of production residue that is not utilized optimally by the community. Dried coffee berry skin waste known as cascara has the potential to be developed into health drink and cosmetic dosage forms. Products designed based on the innovative development of local natural ingredients and the needs of the community in general are in the form of herbal teas, syrups, fermented drinks, face masks, creams and body soaps. Products that utilize coffee pod waste can become the superior product of the Enrekang area which can be produced by empowering the community through MSMEs and continuing to prioritize local local wisdom. Superior products can be created by increasing people's skills through product manufacturing training by taking into account standardized product quality parameters with the aim of obtaining safe and quality products.